CONSTRUCTING RELATIONSHIP BETWEEN SOFTWARE METRICS AND CODE REUSABILITY IN OBJECT ORIENTED DESIGN - M., Manoj H.; N., Nandakumar A. (APTIKOM Journal on Computer Science and Information Technologies, 2016)
The role of design pattern in the form of software metric and internal code architecture for object-oriented design plays a critical role in software en-gineering in terms of production cost efficiency. This paper discusses about code reusability that is a frequently exercised cost saving methodology in IT produc-tion. After reviewing existing literatures towards study on software metrics, we found that very few studies are witnessed to incline towards code reusability. Hence, we developed a simple analytical model that establishes relationship between the design components of standard software metric and code reusability using case studies of three software projects (Customer Relationship Management project, Supply Chain Management project, and Enterprise Relationship Management project). We also testify our proposal using stochastic based Markov model to find that proposed system can extract significant information of maximized values of code reusability with increasing level of uncertainties of software project methodologies.